Evaluating Emergency Remote Assessment Adaptations in Higher Education due to COVID-19: Faculty Insights and Challenges - Elena C. Papanastasiou; Georgia Solomonidou (MDPI AG, 2023)
The purpose of this study was to critically examine the feedback obtained from higher education instructors regarding the implementation of the emergency remote assessment practices that took place within a university in the Republic of Cyprus, in order to identify the strengths and weaknesses of the changes that took place. This was essential since the abruptness of the pandemic did not always allow for smooth transitions during the introduction of these changes. Therefore, the results of this survey study that was based on an online questionnaire identified certain aspects of the assessment adaptations that were evaluated as positive (e.g., the use of e-invigilation software), and other aspects that were not as positive (e.g., performing oral examinations after the written test). However, the results also revealed that cheating and plagiarism were issues that concerned the instructors, as were the technological problems that were faced. All these results are discussed holistically at the end of this article in order to guide further research and decision making regarding online assessments.